2019
DOI: 10.3389/fmicb.2019.02265
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Characterization of Salmonella Isolates From Raw Meat Products Sold at Small Markets in Hubei Province, China

Abstract: Salmonella is a leading cause of foodborne disease and is often associated with the consumption of foods of animal origin. In this study, sixty-six Salmonella isolates were obtained from 631 raw meat samples purchased at small retail suppliers in Hubei Province, China. The most prevalent Salmonella serotypes were Thompson (18.2%) and Agona (13.6%). Frequent antimicrobial resistance was observed for the sulfonamides (43.9%), tetracycline (43.9%), and the β-lactams amoxicillin and ampicillin (36.4% for each). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 54 publications
0
17
1
Order By: Relevance
“…A recent study indicated that integrins and multiple drug resistance genes on mobile plasmids may be responsible for the stable spread of MDR genes in Salmonella ( 39 ). Previous studies on class I integrants in Salmonella in Hubei, Shandong, and Shanxi ( 18 , 39 , 40 ) provinces have found that class I integrants displaying the various antibiotic resistance gene cassettes that are commonly found in Salmonella isolates are associated with provinces, markets, and storage conditions differ. Multiple antibiotic resistance in isolates carrying class I integrons is significantly higher than that seen in isolates lacking these integrons, and they usually show a corresponding antibiotic resistance spectrum to the antibiotic resistance gene cassette contained in their class I integrants.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study indicated that integrins and multiple drug resistance genes on mobile plasmids may be responsible for the stable spread of MDR genes in Salmonella ( 39 ). Previous studies on class I integrants in Salmonella in Hubei, Shandong, and Shanxi ( 18 , 39 , 40 ) provinces have found that class I integrants displaying the various antibiotic resistance gene cassettes that are commonly found in Salmonella isolates are associated with provinces, markets, and storage conditions differ. Multiple antibiotic resistance in isolates carrying class I integrons is significantly higher than that seen in isolates lacking these integrons, and they usually show a corresponding antibiotic resistance spectrum to the antibiotic resistance gene cassette contained in their class I integrants.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of detection of Qnr genes is relatively low among Salmonella species, however, risk of spread of plasmid-mediated Qnr genes through foods is speculated. Quinolone resistant genes were detected in Salmonella species isolated from raw meat products from China (Zhou et al, 2019). Antimicrobial Resistance Pattern of Salmonella Species Recovered from Livestock and Poultry…”
Section: Quinolone Resistancementioning
confidence: 99%
“…In contrast to our findings, high prevalence of bla TEM and bla CTX M was recorded in the Salmonella spp. isolated from retail meat samples by Zhou et al (2019). The worldwide incidence of resistance in Salmonella spp.…”
Section: Beta-lactam Genesmentioning
confidence: 99%
“…enterica serovar Thompson ( S . Thompson) is one of the most frequent Salmonella serovars in humans and is commonly associated with poultry (Shah et al, 2017 ; Eun et al, 2019 ; Qi et al, 2019 ; Zhou et al, 2019 ). S .…”
Section: Introductionmentioning
confidence: 99%
“…Various β-lactamases, including bla CTX−M , bla DHA−1 , and bla SHV , have been reported in S . Thompson isolates (Zhou et al, 2019 ; Elbediwi et al, 2021 ). Reduced susceptibility to FQs is associated with chromosomal mutations and acquisition of AMR genes, such as efflux pumps encoding genes and plasmid-mediated quinolone resistance (PMQR) genes ( qnr, aac(6 ′ )-Ib-cr, oqxAB , and qepA ) (Cuypers et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%